Implementación de la política cultural de Cuba en el telecentro “Telecubanacán” de la provincia Villa Clara - Antón González, Geidy (Universidad Central "Marta Abreu" de Las Villas, 2015)
To know how the means are implementing the politics cultural today, it is a task of high relevancy, because it is in fact in symbolic and cultural levels where the country is facing part of their biggest challenges. It is for it that the present investigation is carried out in the Telecentro "Telecubanacán" of the county Villa Clara, to be this means, one of the most important for the development of the county and they have not been carried out studies of this nature. One works with the objective of characterizing the fundamental features of the implementation of the cultural politics of the telecentro Telecubanacán of the county Villa Clara, using the infrastructural, structural components and superestructural, as analysis subcategories. The investigation was sustained in a qualitative methodology, using a method etnográfico. The sample was selected starting from informants and key informants, being conformed by 30 workers. For the gathering of the information the used instruments were the documental bibliographical revision, analysis of official documents, observation and interviews semiestructuradas and in depth. One keeps in mind for the analysis of the results the triangulation of the information.

Saber cómo los medios están implementando la política cultural hoy, es una tarea de alta pertinencia, porque es precisamente en niveles simbólicos y culturales donde el país está enfrentando parte de sus mayores retos. Es por ello que la presente investigación se realiza en el Telecentro ¨Telecubanacán¨ de la provincia Villa Clara, por ser este medio, uno de los más importantes para el desarrollo de la provincia y no poseer estudios de esta índole. Se trabaja con el objetivo de caracterizar los rasgos fundamentales de la implementación de la política cultural del telecentro Telecubanacán de la provincia Villa Clara, utilizando los componentes infraestructurales, estructurales y superestructurales, como subcategorías de análisis. La investigación se sustentó en una metodología cualitativa, empleando un método etnográfico. La muestra se seleccionó a partir de informantes e informantes claves, quedando conformados por 30 trabajadores. Para la recolección de la información los instrumentos utilizados fueron la revisión bibliográfica documental, análisis de documentos oficiales, observación y entrevistas semiestructuradas y en profundidad. Se tiene en cuenta para el análisis de los resultados la triangulación de la información.
Keywords: Política Cultural; Infraestructura; Estructura; Superestructura.; Cultural Politics; Infrastructure; Structures; Superstructured; Política Cultural; Villa Clara; Televisión